Hubungan Kualitas Layanan Elektronik dan Promosi Penjualan dengan Keputusan Penggunan Platform Pesan Antar Makanan Online di Kota Bandung - Nadila Elsa; Halimah Zahrah (Indonesia Economic Journal, 2026)
This study aims to analyze the influence of E-Service Quality and sales promotion on consumers' usage decisions of GoFood services in Bandung City. Indonesia's food delivery service industry has experienced significant growth with transaction values reaching USD 5.5 billion in 2022 and projected to grow to USD 12.7 billion by 2025. Amid intense competition between GoFood, GrabFood, and ShopeeFood, understanding the factors influencing consumer decisions has become crucial. The research employs a quantitative approach with a causal design to examine cause-and-effect relationships between variables. Primary data were collected through questionnaires distributed to 100 GoFood users in Bandung City using nonprobability sampling with incidental sampling method. Data analysis was conducted using multiple linear regression with hypothesis testing through t-test, F-test, and coefficient of determination. The results indicate that E-Service Quality has a positive and significant effect on GoFood usage decisions, as does sales promotion. Simultaneously, both variables are proven to have a significant influence on GoFood service usage decisions. These findings provide practical implications for digital platforms to enhance electronic service quality and optimize sales promotion strategies in maintaining consumer loyalty in the digital economy era.